2017
DOI: 10.1111/all.13090
|View full text |Cite
|
Sign up to set email alerts
|

The burden of nonadherence among adults with asthma: a role for shared decision‐making

Abstract: To cite this article: Pollard S, Bansback N, FitzGerld JM, Bryan S. The burden of nonadherence among adults with asthma: a role for shared decision-making. AbstractA shared approach to decision-making framework has been suggested for chronic disease management especially where multiple treatment options exist. Shared decision-making (SDM) requires that both physician and patients are actively engaged in the decision-making process, including information exchange; expressing treatment preferences; as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 66 publications
0
26
0
2
Order By: Relevance
“…1 It is estimated that Ͼ300 million people worldwide have asthma, and this disease has caused a significant economic burden. 2,3 The worldwide prevalence of asthma has increased in recent years. 2,4 The complex causes of asthma likely depend on the interaction of environmental, immunologic, and genetic factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is estimated that Ͼ300 million people worldwide have asthma, and this disease has caused a significant economic burden. 2,3 The worldwide prevalence of asthma has increased in recent years. 2,4 The complex causes of asthma likely depend on the interaction of environmental, immunologic, and genetic factors.…”
mentioning
confidence: 99%
“…2,3 The worldwide prevalence of asthma has increased in recent years. 2,4 The complex causes of asthma likely depend on the interaction of environmental, immunologic, and genetic factors. 5,6 Two studies found that asthma is associated with allergic rhinitis, gastrointestinal symptoms, obesity, and psoriasis.…”
mentioning
confidence: 99%
“…In line with current international guidelines in AIT, patients should be selected on the basis of the severity of the disease and on further prerequisites, e.g., a good treatment adherence [53][54][55]. This can easily be achieved using electronic diaries obtained by cell phones as demonstrated in MASK-air ® -a free online app developed for IOS and Andoid-systems by MACVIA-ARIA, an international sentinel network for allergic rhinitis [56][57][58].…”
Section: Placebo Effects In Ait Trials and Considerations For Trial Dmentioning
confidence: 99%
“…Differences in medication adherence are associated with beliefs about medicines in asthma and COPD [ 47 ]. There is a role for shared decision-making to reduce the burden of nonadherence among adults with asthma [ 48 ]. Serious games in asthma education may help to improve adherence [ 49 ].…”
Section: Treatmentmentioning
confidence: 99%